2007
DOI: 10.1017/s1466252307001272
|View full text |Cite
|
Sign up to set email alerts
|

Up to new tricks – A review of cross-species transmission of influenza A viruses

Abstract: Influenza is a highly contagious disease that has burdened both humans and animals since ancient times. In humans, the most dramatic consequences of influenza are associated with periodically occurring pandemics. Pandemics require the emergence of an antigenically novel virus to which the majority of the population lacks protective immunity. Historically, influenza A viruses from animals have contributed to the generation of human pandemic viruses and they may do so again in the future. It is, therefore, criti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 285 publications
(458 reference statements)
0
62
0
Order By: Relevance
“…Infection of pigs with low-pathogenicity avian influenza (LPAI) viruses or seasonal human influenza viruses usually results in limited viral replication with mild clinical disease and lesions, unless the virus adapts through genetic mutation. 77 Even inoculation with viruses such as the 1918 human pandemic H1N1 virus and HPAI H5N1 that induce severe disease in other mammals (humans, primates, ferrets, and mice) only results in disease of similar or less severity than that induced by endemic swine viruses. 82,164 With viruses associated with human disease, challenge studies seeking to identify or characterize virulent strains have of necessity been conducted in animal models, primarily mice, ferrets, and macaques, and in the in vitro studies in influenzasusceptible cell lines.…”
Section: Virulencementioning
confidence: 99%
See 4 more Smart Citations
“…Infection of pigs with low-pathogenicity avian influenza (LPAI) viruses or seasonal human influenza viruses usually results in limited viral replication with mild clinical disease and lesions, unless the virus adapts through genetic mutation. 77 Even inoculation with viruses such as the 1918 human pandemic H1N1 virus and HPAI H5N1 that induce severe disease in other mammals (humans, primates, ferrets, and mice) only results in disease of similar or less severity than that induced by endemic swine viruses. 82,164 With viruses associated with human disease, challenge studies seeking to identify or characterize virulent strains have of necessity been conducted in animal models, primarily mice, ferrets, and macaques, and in the in vitro studies in influenzasusceptible cell lines.…”
Section: Virulencementioning
confidence: 99%
“…Recent receptor studies on the respiratory tracts of humans and swine have revealed very similar distribution patterns, suggesting that avian viruses could just as readily infect the human respiratory tract as the swine respiratory tract, negating the need of the pig as an intermediate host. 142,147 Avian and human viruses do not readily infect swine, 77 but infection of pigs with intact avian and human viruses has been reported. 77,85 The presence of avian-and human-origin genes in the triple reassortants that comprise most of the influenza viruses currently circulating in swine also provides evidence for such infections.…”
Section: Cross-species Infectionsmentioning
confidence: 99%
See 3 more Smart Citations